Productive Zakat Management through the Zakat Community Development Program in Bengkulu Province - Hariya Toni (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This study analyzes the productive zakat management carried out by BAZNAS Bengkulu Province to solve poverty problems. Research is directed by exploring the Zakat Community Development (ZCD) program's planning, implementation, and supervision. This research was conducted with a qualitative approach through case studies. The data was collected through observation techniques, in-depth interviews, and documentation. The results showed that productive zakat management had been carried out well by BAZNAS Bengkulu. This is measured from the realization of the ZCD program from planning to monitoring. In the planning aspect, the ZCD program's realization is carried out by mustahiks through developing business capital, developing competencies, and improving service to consumers. In the implementation aspect, the ZCD program can increase mustahik's income to achieve empowerment in forming a prosperous and independent society. Meanwhile, in the aspect of supervision in the ZCD program, it still needs to be improved so that supervision is carried out to mentor and coach mustahik periodically and continuously.Penelitian ini bertujuan untuk menganalisis manajemen zakat produktif yang dilakukan oleh BAZNAS Provinsi Bengkulu dalam upaya penyelesaian permasalahan kemiskinan. Penelitian menggali proses perencanaan, pelaksanaan dan pengawasan program Zakat Community Development (ZCD). Penelitian ini dilakukan dengan pendekatan kualitatif melalui studi kasus. Pengumpulan data dilakukan dengan observasi, wawancara mendalam dan dokumentasi. Hasil penelitian menunjukkan bahwa manajemen zakat produktif telah dilaksanakan dengan baik oleh BAZNAS Bengkulu. Hal ini diukur dari realisasi program ZCD dari mulai perencanaan sampai dengan pengawasan. Pada aspek perencanaan, realisasi program ZCD dilakukan oleh para mustahik dengan cara pengembangan modal usaha, pengembangan kompetensi dan peningkatan palayanan konsumen. Pada aspek pelaksanaan, program ZCD dipandang mampu meningkatkan penghasilan mustahik sehingga tujuan caturdaya dapat tercapai. Sementara pada aspek pengawasan dalam program ZCD ini masih perlu ditingkatkan, pengawasan dilakukan dengan pendampingan dan pembinaan mustahiq secara berkala dan berkelanjutan.